Caracterização molecular, antigênica e epidemiológica da Ehrlichia canis em Uberlândia, MG, Brasil - Rieck, Susana Elisa (2011)
Canine Monocytic Ehrlichiosis (CME) is a disease with a extensive distribution in Brazil and the world. The etiologic agent is a gram negative obligate intracellular bacterium called Ehrlichia canis, which needs of the vector, Rhipicephalus sanguineus to infect the dog. In 2009 it was carried out the first isolation of this agent in Uberlandia from a sick dog. This isolate was propagated in vitro and the 16S rRNA gene was sequenced for characterization and comparison with other isolates. Sequencing of 16S rRNA confirmed the identification of the isolate as E. canis and showed high homology with other strains and isolates deposited in GenBank. We also evaluated the antigenicity in indirect immunofluorescence assay (IFA), using this antigen and other Brazilian isolate, called São Paulo, and canine sera from both cities. The results by IFA for sera of dogs from São Paulo and Uberlândia were concordant with antigens, despite the variation in the final title. By analyzing the Kappa coefficient, I was noted that the two antigens have different answers, being that the animals from São Paulo, who probably acquired antibodies against the strain isolated from that region, respond similarly to ehrlichia Uberlandia. However, the animals that probably came into contact with E. canis from Uberlândia produced antibodies with higher affinity for antigen Uberlândia. The São Paulo and Uberlândia isolated had different sensitivity to the diagnosis of E. canis by IFA, but not enough to generate false negatives or positives. The prevalence of the disease in canine populations from Uberlândia was tested using the IFA, as well as, probable factors that may influence its occurrence were evaluated. The prevalence of CME was high in Uberlandia, being that 211 (52.8%) dog sera were positive in 400 serum samples. The observation by the owner of the contact of the dogs with ticks did not significantly influenced the occurrence of CME (p = 0.419). There was a trend (p = 0.057) of males to be more positive than females. Dogs over one year old were more positive (56.3%, p = 0.002). Stray dogs were also more positive (68.8%) compared with dogs for donation (34.1%) and with owner (54.8%) (p = 0.002). The place of residence also influenced the positivity, being that the dogs from the districts (76.7%) have higher positivity than from the city (55.9%) and rural area (39.2%) (p = 0.0001). The differences between the localities can be explained by low economic income of the districts when compared with the city, resulting in smaller care of dogs. Uberlândia is endemic to CME, and dogs over one year old, wandering and living in cities with less economic development have a greater predisposition to E. canis infection.